066 Estimating the UK cardiovascular mortality reduction expected with different food policy options. (16th November 2010) - Mateo, G Flores; O'Flaherty, M; Lloyd-Williams, F; Nnoaham, K; Rayner, M; Capewell, S
Abstract : Objective: To estimate the reduction in UK cardiovascular mortality potentially achievable by decreasing saturated fat, trans -fat and salt consumption and fruit and vegetable consumption. Methods: Cardiovascular Disease (CVD) mortality reductions were calculated by synthesising data on population, diet, cholesterol levels, blood pressure, and CVD mortality rates. Contemporary mortality and dietary data among UK adults 25 to 84 years old were obtained from official statistics. We quantified the aetiological effects of specific dietary factors on cholesterol levels, blood pressure, and CVD mortality using systematic reviews and meta-analyses. The number of CVD deaths achievable by reducing saturated fat, trans fat, and salt consumption and fruits and vegetables was estimated for a variety of dietary policy scenarios. Results were stratified by 10-group age and sex. A probabilistic sensitivity analysis was then conducted. Using Monte-Carlo simulation, best, maximum and minimum estimates were calculated. Results: Reducing salt consumption by 1 g/day, saturated fat by 1% of energy intake and trans fat by 0.5%, and of fruits and vegetable intake 1 portion per day would result in approximately 13 850 fewer CVD deaths per year. These would comprise 4790 (minimum estimate 4620, maximum estimate 4910) fewer coronary heart disease deaths among men and 1840 (minimum estimate 1790, maximum estimate 1900) among women, along with 4000(minimum estimate 3910, maximum estimate 4100) fewer stroke deaths in men, 3230 in women (minimum estimate 3160, maximum estimate 3310). Approximately 26% of the 13 850 mortality decrease would be attributed to decreased transaturated fat consumption, 27% to increased fruits and vegetables consumption 24% to decreased saturated fat consumption, and 23% to decreased salt consumption. More substantial dietary improvements could result in approximately 38 100 fewer CVD deaths (min 37 900, max 39 100). Conclusions: The CVD burden attributable to saturated fat, transaturated fat, salt and, fruits and vegetable consumption is substantial. Food policies resulting in even small dietary changes could result in approximately 20 000 fewer CVD deaths each year. This would represent a 9% reduction in UK cardiovascular mortality. Similar benefits might be expected in other industrialised populations.